Pollen morphology of 10 taxa belonging to Prangos Lindl. and Ekimia H. Duman & M.F. Watson (Umbelliferae) from turkey and its taxonomic significance (Bangladesh Journal of Plant Taxonomy, 2009)
Pollen grains of nine taxa of Prangos Lindl. and one of Ekimia H. Duman & M.F. Watson (Umbelliferae) were examined with LM (light microscope) and SEM (scanning electron microscope), and of them four with TEM (transmission electron microscope). The quantitative data were also subjected to cluster analysis. The obtained phenogram revealed that Ekimia bornmuelleri (Hub.-Mor. & Reese) H. Duman & M.F. Watson is strictly different from the taxa of Prangos regarding their quantitative pollen profile; except P. ferulacea Lindl., all taxa included in section Intactae formed a cluster together; members of section Meliocarpoides and section Prangos show a closer relationship regarding their pollen features. Exine ornamentations of Prangos and Ekimia are rugulate-striate and are of no value for identification purposes.